2002
DOI: 10.2307/4146957
|View full text |Cite
|
Sign up to set email alerts
|

Islam and Democracy in the Middle East: The Impact of Religious Orientations on Attitudes toward Democracy in Four Arab Countries

Abstract: Discussions about democracy in the Arab world often include attention to the political orientations of ordinary men and women. In particular, questions are raised about whether popular attitudes and beliefs constitute an obstacle to democratization, possibly because the religious traditions that predominate in most Arab countries inhibit the emergence of a democratic political culture. But while questions are frequently raised about the views of ordinary citizens, about what is sometimes described as "the Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
131
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(159 citation statements)
references
References 11 publications
12
131
1
6
Order By: Relevance
“…It has also been shown that, at the individual level, support for democracy is not necessarily lower among individuals with strong Islamic attachments (e.g. Rose, 2002;Tessler, 2002a;Tessler, 2002b;Toros, 2010). Even if the level of support for democracy is comparable, however, there can be differences in the exact understandings of democracy held by people from the Western world and by those in the Arab world.…”
Section: Democracy and Islammentioning
confidence: 91%
“…It has also been shown that, at the individual level, support for democracy is not necessarily lower among individuals with strong Islamic attachments (e.g. Rose, 2002;Tessler, 2002a;Tessler, 2002b;Toros, 2010). Even if the level of support for democracy is comparable, however, there can be differences in the exact understandings of democracy held by people from the Western world and by those in the Arab world.…”
Section: Democracy and Islammentioning
confidence: 91%
“…These scholars argue for Islam's incompatibility with democracy on the grounds that democracy requires openness, competition, pluralism, and a tolerance of diversity, whereas Islam encourages intellectual conformity and an uncritical acceptance of authority. They also stress that the Islamic tradition does not match with democratic ideals because it vests sovereignty in God, who is the sole source of political power and from whose divine law must emanate all regulations governing the community of believers (Tessler 2002). These scholars' views, therefore, reflect the notion that an Islamic political order must culminate in totalitarianism (Lewis 1994;Choueiri 1996).…”
Section: Islam and Democracy In Western Scholarshipmentioning
confidence: 99%
“…They also assert that there are considerable variations in the interpretations of Muslim religious law advanced by scholars and theologians in Islam and that among these interpretations are positive reflections of democracy, including some by mainstream Islamic theorists (Abed 1995). These scholars insist that openness, tolerance, competition, participation, and progressive innovation are well represented among traditions associated with the religion, and thus entirely compatible with Islam (Esposito and Voll 1996;Tessler 2002). Kramer concludes that Islam has been projected to be congruent with the crucial elements of political democracy, for example, pluralism (within the framework of Islam), political participation, government accountability, the rule of law and the protection of human rights.…”
Section: Islam and Democracy In Western Scholarshipmentioning
confidence: 99%
“…Однако в мусульманских обществах этой связи не наблюдает-ся. Богатые страны Персидского Залива, такие как Саудовская Аравия, Катар, Бахрейн, Кувейт, а также Иран -это отклоняющиеся случаи, показывающие, что богатство не обязательно дает прирост равенства [Tessler, 2002]. Обширный кор-пус текстов доказывает, что в ряде мусульманских обществ права женщин дей-ствительно ущемляются, у них меньше возможностей для образования, карьеры и т. д. Однако этот регион крайне неоднороден: например, в Ливане женщины имеют почти такие же возможности, как в Центральной Европе, в то время как в Йемене или Афганистане, где практикуются браки детей по сговору, только 55 % женщин грамотны (против 85 % мужчин), у них нет паспортов и юридических прав, о равноправии нет и речи [Nussbaum, 2000].…”
Section: теория и предыдущие исследованияunclassified